Changes of inducible NO synthase and Interleukin-1β on the background of experimental rhegmatogenous retinal detachment - Savytskyi, I. V.; Levytska, G. V.; Levytskyi, I. M. (Journal of Education, Health and Sport, 2018)
Purpose: inflammatory processes investigation in the rhegmatogenous retinal detachment pathogenesis and analysis of correction methods effectiveness. On the 7th day in experimental groups observed increase in the interleukin 1β level and inducible NOS activity. On 14th day of the research, as in the 7th, also confirms inflammatory process development. In addition to presence of statistically significant differences between iNOS and IL 1β indices of all experimental groups in comparison with the data of intact animals at the level of significance p <0,05 (and iNOS - at the level of significance p <0,01), the tendency towards increased activation of inflammation in the group that did not receive corrective therapy, and decrease - in group № 4. The most positive therapeutic effect was observed in the 4th group at 21st day. Compared with data of intact rats in group № 2, for given day, increased activity of e inducible NOS at the level of significance was already p <0.01. Differences of group № 3 remained at level of significance p <0,05. In this case, no differences were found when comparing inducible NO-synthase activity in animals of group number 4 and control group. At the same time, there are very significant differences in the comparison of data groups № 4 and № 2. the superiority of the proposed correction suggests decrease in iNOS pathological activity in the rats of the above group compared with the data of the third group (p <0,05). In the analysis IL 1β dynamics at the 21st day, there was no difference in the results of groups number 3 and number 4 in comparison with the values of intact animals. At the same time, difference between fourth group, which received the correction proposed by us in comparison with the data of the second group, in which the simulated pathology was not adjusted, increased. Foregoing confirms the effectiveness of cytokoline and D-asparagine use in complex with the administration of L-arginine 7% solution against the background of experimental rhegmatogenous retinal detachment.